Quest for community : a study in the ethics of order and freedom - Nisbet, Robert A. (New York, 1953)
This book deals with political power-more specifically, with the impact of certain conceptions of political power upon social organization in modern Western society. It begins with what I have called the quest for community, for of all symptoms of the impact of power upon human personality in the contem porary Western world the most revealing seems to me to be the preoccupation, in so many spheres of thought and action, with community-community lost and community to be gained. I do not doubt that behind this preoccupation there lie many historical changes and dislocations-economic, religious, and moral. But I have chosen to deal with the political causes of the manifold alienations that lie behind the contemporary quest for community. Moral securities and allegiances always have a close and continuing connection with the centers and diffusions of authority in any age or culture. Fundamental changes in culture cannot help but be reflected in even the most primary of social relationships and psychological identi fications. Put in these terms, we cannot possibly miss the revo lutionary importance, in modern Western society, of the politi cal State and of idea systems which have made the State preeminent. With all regard for the important social and psycho logical changes that have been induced by technological, eco nomic, and religious forces in modern society, I believe that the greatest single influence upon social organization in the modern West has been the developing concentration of func tion and power of the sovereign political State. To regard the State as simply a legal relationship, as a mere superstructure of power, is profoundly delusive. The real significance of the modern State is inseparable from its successive penetrations of man's economic, religious, kinship, and local allegiances, and its revolutionary dislocations of established centers of function and authority. These, I believe, are the penetrations and dis locations that form the most illuminating perspective for the twentieth-century's obsessive quest for moral certainty and social community and that make so difficult present-day prob lems of freedom and democracy. These are the essential sub ject matter of this book.
Keywords: Sociology